2019
DOI: 10.14292/totbid.dergisi.2019.76
|View full text |Cite
|
Sign up to set email alerts
|

Böbrek hücreli karsinomda kemik metastazı

Abstract: Böbrek hücreli karsinomlar (BHK) böbrek tübüllerinin epitelinden köken alan, bir grup kötü huylu tümördür. Bunlar, tüm yetişkin karsinomlarının %3'ünü kapsar, böbreğin en sık görülen (%90) kötü huylu tümörüdür ve beş yıllık sağkalım oranı %45'tir. Kemik metastazı ikinci en sık metastaz bölgesidir ve metastatik BHK'lerin %30'unda kemik metastazı görülür. BHK kemikte en sık omurga, pelvis ve proksimal femura metastaz yapar. BHK'nin kemoterapi ve radyoterapiye dirençli ve immünoterapiye yanıtının sadece %5-10 ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Bone metastases are most common in the spine, pelvis, and proximal femur. It has been reported that the prognosis of cases with long bone metastases is better than those with spinal and sacrum metastases [2,17]. Bone metastases are considered an independent poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone metastases are most common in the spine, pelvis, and proximal femur. It has been reported that the prognosis of cases with long bone metastases is better than those with spinal and sacrum metastases [2,17]. Bone metastases are considered an independent poor prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…It peaks in the 6th and 7th decades. It is more common in men than in women [2]. There are three main subtypes of RCC: clear cell, papillary, and chromophobe.…”
Section: Introductionmentioning
confidence: 99%